La mer, un vecteur de construction régionale dans l’espace interaméricain ? Une lecture géographique et géopolitique de la maritimisation - Sylvain Domergue (Études Caribéennes)
This article aims to highlight the importance of maritimization in the inter-American space, and its role in the development of regional integration around the issues it raises. In contrast to a traditional reading of the Caribbean basin alone, the study highlights a regionalization of maritime and commercial interactions, as well as illicit flows, around a vast geographical area that includes the Pacific coasts of Central America and Ecuador, the Gulf of Mexico, the Caribbean Sea, and the Atlantic approaches to the Guiana Shield. Field surveys, interviews and analysis of speeches also highlight the willingness of maritime security actors at different levels of governance (States, international organizations, companies, etc.) to focus on the regional prism in order to prevent and fight against transnational maritime risks and threats. This results in the construction of networks and cooperation mechanisms of varying scales, but aiming to place all the actors considered in a relative unity of situation in the face of security issues considered as common. This multi-level cooperation tends to promote regional integration processes through a progressive defragmentation of the maritime space studied, a reduction of border effects between contiguous spatial units (adoption of common equipment, standardization of action protocols, adoption of the same operational language, convergence of regulations, exchange of intelligence and personnel, etc.), and the creation of shared governance spaces, such as Search and Rescue Regions, or the development of multinational maritime protection zones. However, this integration remains incomplete, due to the lack of capacity of many actors and persistent political blockages.